Fatores de risco para queda em idosos residentes em área rural - Vidigal, Fabiana Cristina (2014)
One of the greatest achievements of the contemporary society is the raise of life expectancy. Getting older is, nowadays, a reality in the majority of the developed and in developing societies, becoming a relevant theme in the scientific and public politics point of view, mobilizing researchers and social politic promoters, in the discussion of the challenge that the human longevity is imposing to the societies. A fall is a common problem in the elderly population, and in the rural population, this is also not different. Old people who present a fall historic have serious consequences, including the possibility of a premature death. Thus, this essay had as aim to analyze the risk factors that predispose the fall of the old people dwellers in the rural area, in the city of Cambira, in the State of Parana, Brazil. The essay is based in a quantitative study, described in a transversal delineation with 205 old people, whose ages are equal or over 60 years old, from both genders, in the period within December 2013 and February 2014.The data was collected through individual interviews in the house of the old people. It was used a questionnaire with 22 questions referring to the social-demographic variables and the Mini Mental State Examination (MMSE) was used just as a tool to track the possible cognitive alterations. Besides these, other two tools were applied: a risk of fall scale and a tool to evaluate the functional capability. To analyze the data it was used the Fisher Exact Test. The pattern was heterogenic with the average age of 70,8 years old (Standard deviation dp = 8,3) being 108 (52,6%) masculine individuals and 97 (47,3%) female individuals, the interpretation in the MMSE portrayed that 144 (70,2%) did not present cognitive deficit. Most of the old people living in the rural area who presented a major risk of fall were feminine individuals, with the age equal or over 80 years old, living with a spouse, had up to four years of educational background, family income of one or two minimum wage and had suffered previous falls. It was evidenced that the daily life activities of the Brazilian OARS Multidimensional Functional Assessment Questionnaire - BOMFAQ reflect, in general terms, that the majority of the less aged of the old people developed activities with little or any effort, on the other hand, the older ones presented a lot of difficulty to perform up to five activities of daily life. It was also observed by associating the functional capability with the risk of fall that the old people who present any level of difficulty in the performance of the daily life activities have a high risk factor of fall. The reduction of the functional capability is present as a causal factor as well as consequent to the falls. The data presented help in the comprehension of the inherent functional limitations to the process of aging and allows the nursing department to recognize the elements associated to the risk of falls in the old people population in such a way to aid in the formulation of prevention strategies and adequate health services.